A new species of the Ranunculaceae from southwestern China based on morphological and molecular data - Liu, Bing; Hao, Yun-Qing; Yang, Yong; Sun, Tian-Tian; Lai, Yang-Jun; Zhang, Tao; He, Fei (Phytotaxa, 2016)
Based on field investigations, morphological and molecular systematic studies, a new species, Caltha dysosmoides (Ranunculaceae) from southwestern China is described. It differs from all other known congeneric species by the densely dentate leaf margin, the pendulous pedicels, the scarlet flowers, the compressed filaments, and the triangular connective. To better understand taxonomy of this new species, phylogenetic analyses were conducted using a combined dataset from nrITS, plastid trnL-trnF region, and atpB-rbcL spacer. The results indicate that Caltha is monophyletic and C. dysosmoides is sister to C. sinogracilis. The conservation status of the new species is categorized as CR based on IUCN criteria.